APLIKASI PSIKOLOGI TRANSPERSONAL SEBAGAI PENDEKATAN DALAM KONSELING - Putri, Dhian Riskiana (Universitas Sahid Surakarta, 2022)
Counseling is a service based on psychological theory. Transpersonal which is claimed to be the fourth stream in psychology has its own concept and paradigm in viewing the human psyche. Transpersonal psychology concepts and paradigms have implications for the counseling approach. This study aims to determine the application form of Transpersonal psychology theory as a counseling technique approach. The method used in this research is literature study. The result of this research is the transpersonal approach emphasizes the spiritual side of humans. The counseling method used is by exploring the human spiritual dimension. The ways include meditation, prayer, breathing, and drawing art. The therapist primarily uses intuition and insight to cultivate the interpersonal and spiritual side of the client.